ANALISIS QUANTITY TAKEOFF PADA PEKERJAAN STRUKTUR BAWAH JEMBATAN - Roja Nafiyah; Nunung Martina (Construction and Material Journal, 2022)
Technological developments in the construction sector are expanding, also supported by government regulations. BIM (Building Information Modeling) is one of the technological developments in the construction world. It is expected to help workers minimize errors that will harm the project. Projects that humans still interpret are prone to errors due to human error. This study aims to model three dimensions that function to realize the plan, examine differences in the results of BIM-based quantity takeoff using Autodesk Revit software with conventional methods in one of the bridge structures in Cinere - Jagorawi Toll Project Section 3A, and interview BIM experts with an aim to determine the factors that can affect BIM-based QTO output from the user's perspective. The two QTO outputs produce a difference of ± 0.32% in the volume of the concrete structure and ± 2.28% in the reinforcement volume, where the BIM-based QTO results are lower than the conventional method. The factors that affect the output of BIM-based QTO from the user's point of view, namely (a) the long duration of BIM user’s experience affects the accuracy and details in the modeling, which will affect the QTO output, and(b) the longer the duration of experience and practice time the higher the level of detail and accuracy. The results of the QTO are especially important in determining the overall project cost. An inaccuracy in conducting the QTO will have fatal consequences that can harm the project. Keywords: Autodesk Revit, BIM (Building Information Modeling), Conventional Method, Quantity Takeoff.